2003
DOI: 10.1093/jn/133.5.1390
|View full text |Cite
|
Sign up to set email alerts
|

The Methionine Requirement Is Lower in Neonatal Piglets Fed Parenterally than in Those Fed Enterally

Abstract: The requirements for the sulfur amino acids (SAA), methionine (Met) and cysteine (Cys), have seldom been determined in neonates and to our knowledge have not previously been determined directly in parenterally fed neonates. The sulfur amino acids are catabolized largely in the liver and kidney, and their metabolism by the gut has been studied less frequently. In the present research, the enteral and parenteral Met requirement was determined, without dietary Cys, using the indicator amino acid oxidation (IAAO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 41 publications
4
65
0
Order By: Relevance
“…However, in each of the present experiments, percentage of dose oxidized was almost as reliable, with model regression coefficients very similar to those for absolute oxidation (Table 2). In previous studies, percentage of dose oxidized provided the most reliable estimates of amino acid requirements, with the lowest error in piglets (3,7,18,23,24) and humans (22,27,29). Using any of the output parameters in Table 2, the break point estimates for enterally fed piglets are well within the CI and SEE for parenterally fed piglets.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…However, in each of the present experiments, percentage of dose oxidized was almost as reliable, with model regression coefficients very similar to those for absolute oxidation (Table 2). In previous studies, percentage of dose oxidized provided the most reliable estimates of amino acid requirements, with the lowest error in piglets (3,7,18,23,24) and humans (22,27,29). Using any of the output parameters in Table 2, the break point estimates for enterally fed piglets are well within the CI and SEE for parenterally fed piglets.…”
Section: Discussionmentioning
confidence: 53%
“…The IAAO technique has been demonstrated previously to be an appropriate method of determining amino acid requirements in enterally and parenterally fed piglets (3,7,23,24). Therefore, the IAAO technique was applied to determine both enteral and parenteral tryptophan requirements for neonatal piglets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in neonatal piglets fed cysteine-free diets demonstrated that the whole-body methionine requirement is Ϸ40% lower in total parenterally fed (TPN) compared with enterally fed pigs (31). The difference in this case was attributed to GIT metabolism, because TPN bypasses the gut and results in gut atrophy.…”
Section: Discussionmentioning
confidence: 99%